The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.3917/mav.023.0061
|View full text |Cite
|
Sign up to set email alerts
|

The Corporate Social Responsibility on the Romanian

Abstract: Résumé L’objectif de cet article est l’évaluation du niveau de connaissances et le degré d’implémentation de la responsabilité sociale d’entreprise dans les organisations roumaines. Nous avons évalué l’état actuel de la responsabilité sociale d’entreprise en Roumanie et avons élaboré quelques recommandations pour promouvoir ce concept au niveau national en consensus avec l’objectif stratégique établi en 2002 à Lisbonne. L’économie de l’Europe et l’économie de la Roumanie, comme pays membre de l’Union Européenn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Results showed that the economic downturn had no severe effect on labor standards, while there was an adverse effect on funding and implementing social projects. Şchiopoiu Burlea et al [2010] investigated the influence of financial crisis and corruption on CSR in Romania. The research demonstrated that companies need to pay attention to their ethical sphere and to the institutional legitimacy of the managers' behavior.…”
Section: The Impact Of the Financial Crisis And Economic Downturn Dur...mentioning
confidence: 99%
“…Results showed that the economic downturn had no severe effect on labor standards, while there was an adverse effect on funding and implementing social projects. Şchiopoiu Burlea et al [2010] investigated the influence of financial crisis and corruption on CSR in Romania. The research demonstrated that companies need to pay attention to their ethical sphere and to the institutional legitimacy of the managers' behavior.…”
Section: The Impact Of the Financial Crisis And Economic Downturn Dur...mentioning
confidence: 99%
“…Based on the Integrated Guidelines for Growth and Jobs developed in 2005-2008 by the European Council and the ISO 26000 -International Standard on Social Responsibility, Romania formed an initiative group for an active involvement of the public sector, the private sector and non-governmental sector in implementing a coherent strategy, in order to promote social responsibility in Romania. As the issuer and promoter of public policy, the Romanian Government, through the competent public authorities it has the responsibility to create favorable conditions for developing the concept of social responsibility (Burlea et al 2009). …”
Section: The Strategic Approach Of Social Responsibility In Romaniamentioning
confidence: 99%